Distinguishing mergers and disks in high-redshift observations of galaxy kinematics - Simons, Raymond C.; Ceverino, Daniel (The astrophysical journal, 2019)
The majority of massive star-forming galaxies at z ∼ 2 have velocity gradients suggestive of rotation, in addition to large amounts of disordered motions. In this paper, we demonstrate that it is challenging to distinguish the regular rotation of a disk galaxy from the orbital motions of merging galaxies with seeing-limited data. However, the merger fractions at z ∼ 2 are likely too low for this to have a large effect on measurements of disk fractions. To determine how often mergers pass for disks, we look to galaxy formation simulations. We analyze ∼24,000 synthetic images and kinematic maps of 31 high-resolution simulations of isolated galaxies and mergers at z ∼ 2. We determine if the synthetic observations pass the criteria commonly used to identify disk galaxies and whether the results are consistent with their intrinsic dynamical states. Galaxies that are intrinsically mergers pass the disk criteria for anywhere from 0% to 100% of sightlines. The exact percentage depends strongly on the specific disk criteria adopted and weakly on the separation of the merging galaxies. Therefore, one cannot tell with certainty whether observations of an individual galaxy indicate a merger or a disk. To estimate the fraction of mergers passing as disks in current kinematics samples, we combine the probability that a merger will pass as a disk with theoretical merger fractions from a cosmological simulation. Taking the latter at face value, the observed disk fractions are overestimated by small amounts: at most by 5% at high stellar mass (1010-11 M ⊙) and 15% at low stellar mass (109-10 M ⊙).